(untitled) (Journal of the College of Basic Education, 2025)
Intestinal diseases are considered health problems that lead to the emergence of harmful microbes that are resistant to many drugs and the use of natural materials poses a great challenge to health as they increase their ability to reduce the symptoms of potentially fatal infectious diseases. Objective: This study aimed to use alternative plants to be approve as drugs to reduce the ability of the bacteria. Methods: Ginger root extract was prepared and tested using the minimum inhibitory concentration (MIC) technique. Its inhibitory activity against four bacterial isolates was evaluated using agar plates. The extract’s effect was compared with that of a standard antibiotic (trimethoprim). In addition, chemical analysis was performed to identify the plant’s active ingredients using chromatography techniques. Results: The results showed that Ginger alcoholic extract was able to had excellent antibacterial activity, which was determined by investigating the minimum inhibitory concentration by taking different concentrations (2-1024 µg/mL). The anti-biofilm activity of the four Salmonella was determined and the results showed that the inhibition by zone ranged between 20-26 mm for the extract of ginger roots compared to the Trimethoprim drug. Conclusions: Ginger Alcoholic extract represents a suitable alternative to chemical antibiotics to combat Salmonella bacteria